2021
DOI: 10.36076/ppj.2021.24.e771
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation for the Management of Neuropathic Pain: A Narrative Review

Abstract: BACKGROUND: Neuropathic pain (NP) is common and often resistant to conventional analgesics. Among different types of noninvasive brain stimulation techniques, transcranial direct current stimulation (tDCS) has been widely used to mitigate pain in patients with NP. OBJECTIVE: The aim of this study was to review the effects of tDCS on the management of various types of NP. STUDY DESIGN: Narrative review. METHODS: A PubMed search was conducted for articles published until October 1, 2020, using tDCS to treat N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Neuropathic pain is a chronic pain type which is often resistant to available analgesics [20][21][22] and therefore, much effort is made to find novel methods to cope with this serious clinical issue. In this context, there is a strong need for new analgesic drug candidates able to attenuate the main symptoms of neuropathic pain, i.e., mechanical and thermal hypersensitivity resulting in tactile and thermal allodynia and hyperalgesia [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is a chronic pain type which is often resistant to available analgesics [20][21][22] and therefore, much effort is made to find novel methods to cope with this serious clinical issue. In this context, there is a strong need for new analgesic drug candidates able to attenuate the main symptoms of neuropathic pain, i.e., mechanical and thermal hypersensitivity resulting in tactile and thermal allodynia and hyperalgesia [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike DBS, tDCS is a non-invasive technique of brain stimulation to regulate neuronal activity in the motor cortex. tDCS has been shown to mitigate neuropathic pain in patients with SCI ( Yang and Chang, 2021 ). tDCS with rehabilitation training augmented adaptive plasticity and promoted recovery of upper limb function in participants with incomplete tetraplegia ( Potter-Baker et al, 2017 ).…”
Section: Therapeutic Strategies For Spinal Cord Repairmentioning
confidence: 99%
“…One tDCS technique has shown beneficial outcomes in alleviating neuropathic pain associated with traumatic spinal cord injury, stroke, multiple sclerosis, fibromyalgia, trigeminal neuralgia and diabetes [ 198 ]. A randomized controlled trial conducted by Straudi et al showed significantly reduced pain and increased psychological well-being after the use of tDCS in patients with chronic low back pain compared with a sham-tDCS group [ 219 ].…”
Section: Treatment Strategies For Neuropathic Painmentioning
confidence: 99%